2004
DOI: 10.1002/jbm.b.30166
|View full text |Cite
|
Sign up to set email alerts
|

Static mechanical properties of hydroxyapatite (HA) powder‐filled acrylic bone cements: Effect of type of HA powder

Abstract: This work reports on the effect of the amount (0, 10, and 30 wt %) and type of HA powder incorporated into an acrylic bone cement on the tensile properties, compression properties, and fracture toughness. The three different types of HA powders used were synthesized in the laboratory and coated with a silane agent prior to incorporation into the cement powder, and differed in particle size, water content, surface area, and crystallinity. It was found that the inclusion of any type of HA powder led to an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 25 publications
3
27
0
Order By: Relevance
“…In the literature these variations are attributed to the fact that glasses containing around 50 wt % of P 2 O 5 (methaphosphate glasses) are very difficult to obtain preserving its exact chemical composition. 26 The presence of the functional groups from the silane agent in the FTIR spectra for both silanated glasses corroborates the efficiency of the silanation process. XPS characterization enabled the identification of the major surface components on untreated and …”
Section: Glass Powder Characterizationsupporting
confidence: 58%
“…In the literature these variations are attributed to the fact that glasses containing around 50 wt % of P 2 O 5 (methaphosphate glasses) are very difficult to obtain preserving its exact chemical composition. 26 The presence of the functional groups from the silane agent in the FTIR spectra for both silanated glasses corroborates the efficiency of the silanation process. XPS characterization enabled the identification of the major surface components on untreated and …”
Section: Glass Powder Characterizationsupporting
confidence: 58%
“…On the other hand, previous studies have suggested that these behaviors of PMMA/HAc composite in terms of mechanical and tribological properties can be explained by the role of HA particles in the composite structure ( Ref 11,[22][23][24][25]. When a small amount of HA particles is distributed homogeneously, the HA particles behave as load carriers, leading to enhancement of the mechanical and tribological properties.…”
Section: Resultsmentioning
confidence: 91%
“…When a small amount of HA particles is distributed homogeneously, the HA particles behave as load carriers, leading to enhancement of the mechanical and tribological properties. However, when the proportion of the HA particles increases, a nonhomogeneous distribution can occur, resulting in aggregation of particles with poor adhesion to the matrix and leading to a reduction in the mechanical and tribological properties ( Ref 11,[22][23][24][25]. The results obtained in the present work are also consistent with these reports such that the mechanical and tribological properties of nano-composite cement increase by incorporating HAc nano-particles up to a certain percentage, i.e., 10 wt.%, and further addition of HAc decreases these properties.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the addition of inorganic fillers makes the bone cement brittle because of the low ductility of the fillers and the weak interface bonding between the fillers and the matrix. Various studies have demonstrated that improved adhesion between filler and matrix resulted in the enhanced mechanical properties of the cement [9,[25][26][27][28]. One approach could be the surface modification of the inorganic fillers before mixing to improve the interaction between the fillers and the matrix.…”
Section: Sr-ha Bone Cement Surface Modificationmentioning
confidence: 97%
“…With the aim of replacing the traditional PMMA bone cement, some bioactive bone cements were developed. PMMA filled with inorganic fillers [6][7][8][9] or bisphenol A diglycidylether dimethacrylate (Bis-GMA) filled with inorganic fillers was commonly studied [10][11][12][13]. The incorporation of a bioactive filler into the organic based bone cement can partially increase the biocompatibility, as well as osteo-conductivity.…”
Section: Introductionmentioning
confidence: 99%